Hybrid Materials: Optochemically Responsive 2D Nanosheets of a 3D Metal–Organic Framework Material (Adv. Mater. 27/2017). Issue 27 (July 2017) - Chaudhari, Abhijeet K.; Kim, Ha Jin; Han, Intaek; Tan, Jin‐Chong
Abstract : The concept of "host–guest self‐assembly" is used to create a metal–organic framework (MOF) that serves as a host to entrap light‐emitting guest molecules. This unique host–guest assembly, described by Jin‐Chong Tan and co‐workers in article number1701463, gives rise to bespoke materials exhibiting tunable optical and electronic properties, which are extremely sensitive photochemical sensors for practical applications. The thin‐film optochemical sensors experience different blue‐/redshifts when constructed from nanosheets of this host–guest material.